Psychological well-being and their relationship with different referents and sources of happiness in Chile - Moyano-Diaz, Emilio (2021)
The association between nine philosophical referents of happiness and well-being was examined in a convenience sample (n= 1060) of two Chilean cities. Participants had to choose one referent and respond to well-being, satisfaction, and happiness scales regarding family, friends, work, and leisure. A lower educational level was associated more with the referents Tranquility and Stoicism and less with the realization of capabilities. Young people ascribe more to the referents Satisfaction and Carpe Diem. Multiple hierarchical regressions considering well-being as a predicted variable showed that the Satisfaction and Affiliation referents were associated with greater psychological well-being. These results and the differences between the happiness referents chosen according to the controlled variables are discussed.